Conventional Farming Practices around Kathmandu Valley: An Appraisal - Kharel, Suman; Marahatta, Deepak (Nepalese Journal of Development and Rural Studies, 2020)
Conventional farming is a new area of research in developing countries. It is rooted in industrial agriculture andfocuses on production as heavily. It demands a high amount of chemical fertilizers. The research follows a case study under the interpretive paradigm using multiple sources of evidence such as interviews, observations, and surveys ofthe literature. Usual to most conventional practices, the local inbreeds of crops are replaced by high yielding varieties of crops. One of the main advantages of conventional farming is the application of a higher amount ofagricultural inputs. The study has shown that the availability of transport made it easy to reach products to the market and has contributed to increasing the income of the farmers. Inadequate knowledge of the use of fertilizers and pesticides results in the origins of new diseases in crops is a major challenge of conventional farming. This research concludes that commercial organic farming can be an alternative to conventional farming. The finding shows the need for agricultural training and capacity building of farmers and also the need to provide subsidies so that farming will be more lucrative.